Effect of molecular shape of suspended colloids on an osmotic flow across a fibrous membrane. (18th May 2020) - Yooprasertchuti, Kittipitch; Dechadilok, Panadda
Highlights: Colloid shape affects its osmotic reflection coefficients ( σv ) in fibrous membranes. Serum albumin molecular shape contributes to fluid extravasation prevention. Serum albumin molecular shape also helps reducing its loss from microcirculation. Membrane fiber volume fraction reduction causes a decrease in σv of spheroids . Abstract: Effects of colloid molecular shape on osmotic reflection coefficients ( σv ) in a liquid-filled hexagonal array of cylinders are investigated by employing lubrication theory. Results demonstrate that, for spheroids with equal Stokes-Einstein radius ( aSE ), an increase in the deviation from unity of the axial ratio ( γ ) corresponds to an increased σv . If the fiber matrix geometry is that of the quasiperiodic substructure of the glycocalyx layer adjacent to endothelial surfaces, believed to be the primary barrier for serum albumins, σv of a spheroid with aSE close to that of serum albumins is larger than σv of a sphere, and close to experimentally obtained σv of serum albumins even when the electrostatic interaction is not included, suggesting that serum albumin molecular shape contributes to its ability to prevent intravascular fluid extravasation, and, given the close correspondence between osmotic and filtration reflection coefficients, helps minimize albumin loss from microcirculation.